IDENTIFIKASI LOGAM BERAT PADA AIR KOLONG DAN MIKROBA POTENSIAL UNTUK BIOREMEDIASI DI LAHAN PASCA PENAMBANGAN TIMAH - asep kurnia (PPSDM Geominerba, 2023)
The Bangka Belitung Islands Province is one of the largest tin producing regions in Indonesia. The purpose of this study was to identify the status of heavy metals in pit water and potential microbes for bioremediation in post-tin mining land. Heavy metals and Cr in water were detected at all locations (n ​​= 12), while Pb, Cd, Mn and Zn were detected at 4, 5, 2 and 3 locations respectively. The minimum concentration of these heavy metals was not detected except Cr metal which was 0.02 mg/l, while the maximum concentrations of Pb, Cd, Mn, Zn and Cr were 0.06; 0.07; 0.72; 0.29; and 0.03 mg/l. The results of isolation of soil samples from post-tin mining land on Bangka Island show that there are isolates of bacteria, fungi and Azotobacter which have the potential to remediate heavy metal polluted land. The number of bacterial isolates in the bulk soil and rhizosphere ranged from 1-2 isolates, while for fungi both in the bulk soil and in the rhizosphere ranged from 1-4 isolates. In the bulk soil sample, Azotobacter isolates were obtained. Total bacterial colonies in bulk soil were 106 cfu/g soil and 103 cfu/g soil for fungi, while in the rhizosphere it ranged between 105-106 and 102 cfu/g soil for bacteria and fungi respectively.